Prácticas éticas en las empresas : importancia, tipología y desafíos - Pasco Dalla Porta, Mario (2022)
This academic note deals with business ethics practices. In this vein, it explains their importance regarding the organizations’ management, then it distinguishes the main categories of ethical practices, and subsequently it presents some challenges that face their implementation. In addition, the document reports the situation of these practices in the main companies in Peru.